Cancer surveillance in longstanding ulcerative colitis: endoscopic appearances help predict cancer risk. Issue 12 (11th November 2004) - Rutter, M D; Saunders, B P; Wilkinson, K H; Rumbles, S; Schofield, G; Kamm, M A; Williams, C B; Price, A B; Talbot, I C; Forbes, A
Abstract : Background and aims: The risk of colorectal cancer is increased in ulcerative colitis (UC). Patients with UC have diverse colonoscopic appearances. Determining colonoscopic markers for cancer risk could allow patient risk stratification. Patients and methods: Following on from an earlier study which demonstrated a correlation between inflammation severity and neoplasia risk, a case control study was performed to look for colonoscopic markers of colorectal neoplasia risk in UC. Each patient with neoplasia detected between 1988 and 2002 was matched with two non-dysplastic colitic controls. Data were collected on post-inflammatory polyps, scarring, strictures, backwash ileitis, a shortened, tubular, or featureless colon, severe inflammation, and normal looking surveillance colonoscopies. Results: Cases (n = 68) and controls (n = 136) were well matched. On univariate analysis, cases were significantly more likely to have post-inflammatory polyps (odds ratio (OR) 2.14 (95% confidence interval 1.24–3.70)), strictures (OR 4.22; 1.08–15.54), shortened colons (OR 10.0; 1.17–85.6), tubular colons (OR 2.03; 1.00–4.08), or segments of severe inflammation (OR 3.38; 1.41–10.13), and less likely to have had a macroscopically normal looking colonoscopy (OR 0.40; 0.21–0.74). After multivariate analysis, a macroscopically normal looking colonoscopy (OR 0.38; 0.19–0.73), post-inflammatory polyps (2.29; 1.28–4.11), and strictures (4.62; 1.03–20.8) remained significant. The five year risk of colorectal cancer following a normal looking colonoscopy was no different from that of matched general population controls. Conclusions: Macroscopic colonoscopic features help predict neoplasia risk in UC. Features of previous/ongoing inflammation signify an increased risk. A macroscopically normal looking colonoscopy returns the cancer risk to that of the general population: it should be possible to reduce surveillance frequency to five years in this cohort.